Pengaruh Human Skill dan Technical Skill terhadap Kinerja Pelayanan di Kantor Kecamatan Bojongloa Kidul Kota Bandung - Cindy Helmalia Anjani; Sri Suwarsi; Allya Roosallyn Assofya (UNISBA Press, 2023)
Abstract. Service performance has a very important role for a public sector, where this refers to the level of success in carrying out tasks and the ability to achieve the goals that have been set. In this study, service performance is based on human skills and technical skills (Akbar, 2018). Human Skills are influenced by the specific skills of employees that can be competitive, including education and training that can help in solving problems, while Technical Skills are related to the individual character of employees based on the level of ability. This study aims to determine and analyze Human Skills, Technical Skills, service performance, and the influence of Human Skills and Technical Skills on service performance. The method used in this research is descriptive and verification method, with a quantitative approach based on data processing through SPSS 25 software. The sampling technique in this study used a total sampling of 62 employees of the Bojongloa Kidul District Office. The results of this study conclude that: 1) Human skills in the District of Bojongloa Kidul, Bandung City are in the bad category. 2) Technical skills in the District of Bojongloa Kidul, Bandung City are in the very bad category. 3) Service performance in the District of Bojongloa Kidul, Bandung City is in a fairly good category. 4) There is a positive and significant influence of human skills on service performance of 20.3%. 5) There is a positive and significant influence of technical skills on service performance of 11.5%. Abstrak. Kinerja pelayanan memiliki peran yang sangat penting bagi sebuah sektor publik, dimana hal ini mengacu pada tingkat keberhasilan dalam melakukan tugas dan kemampuan untuk mencapai tujuan yang telah ditetapkan. Pada penelitian ini kinerja pelayanan didasarkan pada human skill dan technical skill (Akbar, 2018). Human Skill dipengaruhi oleh keterampilan khusus karyawan yang dapat kompetitif meliputi pendidikan dan pelatihan yang dapat membantu dalam penyelesaian masalah, sedangkan Technical Skill ini berkaitan dengan karakter individu pegawai berdasarkan tingkat kemampuan. Penelitian ini bertujuan untuk mengetahui dan menganalisis Human Skill, Technical Skill, kinerja pelayanan, serta pengaruh Human Skill dan Technical Skill terhadap kinerja pelayanan. Metode yang digunakan dalam penelitian ini yaitu metode deskriptif dan verifikatif, dengan pendekatan kuantitatif berdasarkan pengolahan data melalui software SPSS. Teknik pengambilan sampel pada penelitian ini menggunakan total sampling sebanyak 62 orang pegawai Kantor Kecamatan Bojongloa Kidul. Hasil penelitian ini menyimpulkan bahwa : 1) Human skill di Kecamatan Bojongloa Kidul Kota Bandung dalam kategori buruk. 2) Technical skill Kecamatan Bojongloa Kidul Kota Bandung dalam kategori sangat buruk. 3) Kinerja Pelayanan Kecamatan Bojongloa Kidul Kota Bandung dalam kategori cukup baik. 4) Terdapat pengaruh positif dan signifikan human skill terhadap kinerja pelayanan sebesar 20,3%. 5) Terdapat pengaruh positif dan signifikan technical skill terhadap kinerja pelayanan sebesar 11,5%.